“TRISNA” Conceptual Model and Spiritual Approach to Build Body Image, Self-Esteem, and Quality of Life in Cervical Cancer Patients at Dr. Moewardi Hospital, Surakarta, Indonesia - Rita Benya Adriani; Siti Handayani; Tri Prabowo (Indonesian Journal of Medicine, 2023)
Background: The problems of cervical cancer patient’s psychological response to advanced cancer are acute crisis, struggle, anxiety, and sadness, which will interfere with their life, especially sexual relations with their partners. Sexual relations in the Javanese view are a noble, sacred bond and have the function to maintain harmony. The spiritual approach and "TRISNA" which contains the principles of Javanese teachings about sincerity should be applied by cervical cancer patients and their sexual partners. This study aimed to determine the effect of palliative sexuality treatment with a "TRISNA" and spiritual approach to body image, self-esteem, and quality of life in cervical cancer patients at Moewardi Hospital Surakarta.Subjects and Method: This study was a quasi-experimental design using 138 samples divided into three groups, namely the TRISNA, Spiritual, and control groups with a pre-test-post-test control group design conducted at Dr. Moewardi Hospital Surakarta, Central Java, in May to August 2019. The dependent variable in this study is the body image scale, self-esteem, and quality of life. The independent variables in this study are the TRISNA and spiritual approaches. The instruments used are the body image scale, self-esteem scale, and the European Organization for Research and Treatment of Cancer (EORTC) QOQ-CX24. Statistical analysis using t-test with SPSS 13 application software.Results: The results showed that sexuality with the TRISNA and spiritual approaches can improve body image (F= 137.67), self-esteem (F= 241.05), and quality of life (F= 76.95) of cervical cancer patients with a significant value for each group (p≤0.001).Conclusion: Sexuality with TRISNA's approach is the most influential in body image, self-esteem, and quality of life in cervical cancer patients in cervical patients Moewardi Hospital Surakarta.Keywords: body image scale, self-esteem, quality of life, sexuality, spiritualCorrespondence: Rita Benya Adriani, Ministry of Health of Surakarta, Health Polytechnics Surakarta, Letjend Sutoyo Street, Mojosongo, Surakarta 57127, Central Java, Indonesia. Email: benyaadriani@gmail.com. Mobile +628122617033.Indonesian Journal of Medicine (2023), 08(01): 37-46https://doi.org/10.26911/theijmed.2023.08.01.04